MANAGEMENT OF ACUTE CORONARY SYNDROMES DURING PREGNANCY: A RETROSPECTIVE ANALYSIS OF PCI INTERVENTIONS IN PAKISTANI HOSPITALS - Dr Syed Muzammil Shah; Dr Honey Raj Vishno; Dr Tariq Shah; Dr Muhammad Abdul Wahab; Dr Rafi Ullah; Dr Rukhana (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Acute Coronary Syndromes (ACS) encompass conditions such as unstable angina, non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI), characterized by sudden reduced blood flow to the heart. The management of ACS has traditionally relied on medical therapy, thrombolysis, and percutaneous coronary intervention (PCI), with PCI being the preferred strategy due to its efficacy. However, managing ACS during pregnancy presents unique challenges due to physiological changes and the need to balance maternal and fetal safety. Objective: This study aimed to evaluate the management and in-hospital outcomes of pregnant women with ACS undergoing PCI in Pakistani hospitals. Methods: A retrospective analysis was conducted on pregnant women aged 18-45 years diagnosed with ACS who underwent PCI across multiple Pakistani hospitals from January 2018 to December 2022. The study excluded patients with prior coronary artery bypass grafting, terminal non-cardiovascular illnesses, or those who did not consent. Data were collected from medical records and analyzed using SPSS version 25.0. The primary outcomes assessed were the incidence of Major Adverse Cardiovascular Events (MACE) during hospitalization, including myocardial infarction (MI), target vessel revascularization (TVR), and cardiovascular death. Secondary outcomes included left ventricular ejection fraction (LVEF) post-PCI, hospital length of stay, and complications such as bleeding and stroke. Results: The study included 300 pregnant women with ACS undergoing PCI. The mean age of the patients was 32.4 years (SD: 4.5 years). The overall incidence of MACE was 18.7%, with 7.3% experiencing MI, 6.0% undergoing TVR, and 5.3% resulting in cardiovascular death. The mean LVEF post-PCI was 50.2% (SD: 9.8%), and the median hospital stay was 6 days (IQR: 4-9 days). Significant differences in primary outcomes were observed between hypertensive and non-hypertensive patients, with hypertensive patients showing higher incidences of MACE (33.3% vs. 12.4%, p<0.001). Conclusion: The management of ACS during pregnancy via PCI in Pakistani hospitals reveals significant in-hospital outcomes. The high incidence of MACE and other complications underscores the need for specialized care and monitoring for pregnant women undergoing PCI. These findings provide valuable insights for clinicians and highlight the necessity for further research to develop standardized protocols and improve clinical outcomes in this unique patient population.